The boat is full - Engel, Tina; Bois, Curt 1901-1991 (Home Vision Entertainment, 2006)
A group of Jewish refugees attempt to escape to Switzerland from Nazi Germany by posing as a family
Dt. mit engl. Untertiteln
Keywords: Haesler, Alfred A.; Jewish refugees / Government policy / Switzerland / Drama; World War, 1939-1945 / Jews / Switzerland / Drama; Juden; Politik; Weltkrieg (1939-1945); Schweiz